A synapsin Ⅰ cleavage fragment contributes to synaptic dysfunction in Alzheimer's disease. Issue 5 (20th April 2022) - Meng, Lanxia; Zou, Li; Xiong, Min; Chen, Jiehui; Zhang, Xingyu; Yu, Ting; Li, Yiming; Liu, Congcong; Chen, Guiqin; Wang, Zhihao; Ye, Keqiang; Zhang, Zhentao
Abstract: Synaptic dysfunction is a key feature of Alzheimer's disease (AD). However, the molecular mechanisms underlying synaptic dysfunction remain unclear. Here, we show that synapsin Ⅰ, one of the most important synaptic proteins, is fragmented by the cysteine proteinase asparagine endopeptidase (AEP). AEP cleaves synapsin at N82 in the brains of AD patients and generates the C‐terminal synapsin Ⅰ (83–705) fragment. This fragment is abnormally distributed in neurons and induces synaptic dysfunction. Overexpression of AEP in the hippocampus of wild‐type mice results in the production of the synapsin Ⅰ (83–705) fragment and induces synaptic dysfunction and cognitive deficits. Moreover, overexpression of the AEP‐generated synapsin Ⅰ (83–705) fragment in the hippocampus of tau P301S transgenic mice and wild‐type mice promotes synaptic dysfunction and cognitive deficits. These findings suggest a novel mechanism of synaptic dysfunction in AD. Abstract : Asparagine endopeptidase is activated in an age‐dependent manner in the brain. Active AEP cleaves synapsin I and generates the synapsin I C83 fragment, which affects the recycling of synaptic vesicles and causes synaptic dysfunction and cognitive impairment, promoting the onset of AD.